An Analysis of the Quality of Odd Semester Final Examination Items in Indonesian History Subject for Grade XII Social Science Students at SMAN 7 Kota Serang Academic Year 2024/2025: Analisis Kualitas Butir Soal Penilaian Akhir Semester (PAS) Ganjil Mata Pelajaran Sejarah Indonesia Kelas XII IPS di SMAN 7 Kota Serang Tahun Ajaran 2024/2025 - Shalama Qaulum Fadilla; Arif Permana Putra; Rikza Fauzan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyze the quality of test items used in the Odd Semester Final Examination (Penilaian Akhir Semester/PAS) for the Indonesian History subject of Grade XII Social Science students at SMAN 7 Kota Serang in the 2024/2025 academic year. The analysis focuses on the appropriateness of the items in terms of content, construction, and language, as well as their psychometric characteristics, including validity, reliability, difficulty level, discrimination power, and distractor effectiveness. This research employed a descriptive quantitative approach. The subjects were Grade XII Social Science students, and data were collected through documentation of test items and students’ answer sheets. The data were analyzed descriptively using an item review format and quantitatively using Microsoft Excel and Anates version 4. The results indicate that, overall, the quality of the test items was fairly good and aligned with the basic competencies. However, several items were found to be inconsistent with the specified indicators and required improvement in terms of construction and language. The item validity analysis showed that 60% of the items were valid, while 40% were invalid. The reliability coefficient was 0.52, indicating a moderate level of reliability. In terms of discrimination power, the items ranged from weak to very good, while the difficulty level analysis revealed that most items were categorized as moderate. Regarding distractor effectiveness, some items contained less functional distractors. This study highlights the importance of systematic item analysis to ensure the quality of assessment instruments and recommends continuous collaboration among teachers, schools, and the MGMP to improve learning evaluation practices.